Upgrade : taking your work and life from ordinary to extraordinary - Florida, Rana (McGraw-Hill Education, 2013)
Instead of developing a real strategy to upgrade and optimize our lives, too many of us just slog through life in a state of "managed dissatisfaction." But it's never too late to envision an entirely different futuree--or to actively upgrade your life. It's not about finding more time, money, or resources. Anyone can do it. This smart and entertaining guide delves deep into each principle, giving you the insights, tools, and inspiration to take your life from ordinary to extraordinary.